2018
DOI: 10.1097/pas.0000000000001056
|View full text |Cite
|
Sign up to set email alerts
|

Histologic and Outcome Study Supports Reclassifying Appendiceal Goblet Cell Carcinoids as Goblet Cell Adenocarcinomas, and Grading and Staging Similarly to Colonic Adenocarcinomas

Abstract: Goblet cell carcinoid tumors are amphicrine tumors whose biological behavior ranges from indolent to highly aggressive, depending on tumor grade. Current grading systems for these tumors are based on identifying an adenocarcinoma arising in the setting of a goblet cell carcinoid tumor, which distinguishes this tumor from other gastrointestinal tract adenocarcinomas. Because goblet cell tumors are predominantly tumors of mucin secreting cells, we propose that they be classified as goblet cell adenocarcinomas, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
81
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(82 citation statements)
references
References 20 publications
1
81
0
Order By: Relevance
“…A recent study on the clinicopathological, immunohistochemical and molecular features of a series of 10 cases (eight gastric and two intestinal neoplasms) has shown that amphicrine neoplasm is a unique entity with distinct biological and histological features. 68 In this study, the histological three-tiered grading proposed by Yozu et al for appendiceal goblet cell adenocarcinoma 69 proved to be also effective in gastric and intestinal amphicrine neoplasms for predicting prognosis, also independently from disease stage. 68 Pancancer transcriptome analysis revealed that amphicrine neoplasms have similarities with adenocarcinomas, but not with NENs.…”
Section: A M P H I C R I N E C a R C I N O M A Smentioning
confidence: 59%
“…A recent study on the clinicopathological, immunohistochemical and molecular features of a series of 10 cases (eight gastric and two intestinal neoplasms) has shown that amphicrine neoplasm is a unique entity with distinct biological and histological features. 68 In this study, the histological three-tiered grading proposed by Yozu et al for appendiceal goblet cell adenocarcinoma 69 proved to be also effective in gastric and intestinal amphicrine neoplasms for predicting prognosis, also independently from disease stage. 68 Pancancer transcriptome analysis revealed that amphicrine neoplasms have similarities with adenocarcinomas, but not with NENs.…”
Section: A M P H I C R I N E C a R C I N O M A Smentioning
confidence: 59%
“…These tumors can have variable biological behavior from indolent to highly aggressive depending on the tumor grade. 64 Low-grade tumors are typically arranged predominantly in tubules and usually involve the wall of the appendix circumferentially without eliciting a stromal reaction (Figure 7, A through D). Some tumor cells are not arranged in tubules and appear as clusters of cohesive goblet-like cells.…”
Section: Appendiceal Goblet Cell Adenocarcinomamentioning
confidence: 99%
“…In this system, tumors with a tubular or clustered growth pattern more than 75% are considered low-grade, those with 50% to 75% tubular or clustered growth pattern are intermediate grade, and if the tumor shows less than 50% tubular or clustered growth pattern, it is qualified as highgrade. 64 A similar three-tiered system was used by Tang et al 65 in the past.…”
Section: Appendiceal Goblet Cell Adenocarcinomamentioning
confidence: 99%
“…The peritoneal metastases of goblet cell adenocarcinoma were classified into Grade 1 (G1), Grade 2 (G2) and Grade 3 (G3) groups, according to the WHO classification, 7 and into groups A, B, and C, according to the Tang classification. 5 High-grade architectural patterns were recorded as goblet/signet ring-like cells with single-cell infiltration or large irregular aggregates, gland-forming adenocarcinoma, and a singlefile/anastomosing cords/sheet-like growth pattern of predominantly non-goblet cells, as described by Yozu et al 8 The percentage of tumour consisting of highgrade architectural patterns was recorded. The presence and proportion of extracellular mucin within the tumour were also recorded (absent, <50%, or >50%).…”
Section: P a T H O L O G I C A L E V A L U A T I O Nmentioning
confidence: 99%
“…Several studies have shown that the proportion of high-grade carcinoma growth patterns in a goblet cell adenocarcinoma is predictive of prognosis, and multiple grading systems have been proposed centred around this concept. [3][4][5][6] The WHO 5th edition grading system is three-tiered and based on the proportion of tumour consisting of low-grade and high-grade patterns, 7 as described by Yozu et al 8 Peritoneal spread is the most common route of metastasis in goblet cell adenocarcinoma, with up to half of female patients presenting with ovarian metastases. 5,9,10 Peritoneal dissemination is also the most common cause of disease-specific death in patients with goblet cell adenocarcinoma.…”
Section: Introductionmentioning
confidence: 99%